2009
DOI: 10.2174/1874076600903010034
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of In-Hospital Mortality after Acute Ischemic Stroke in Subjects with and without Diabetes Mellitus

Abstract: Abstract:Background: Diabetes mellitus is a well-established risk factor for ischemic stroke and is associated with increased in-hospital mortality. The aim of the present study was to determine the potential predictors of in-hospital mortality after an ischemic stroke in diabetic and nondiabetic subjects. Methods: 159 diabetic subjects (66 males / 93 females, mean age ± SD: 77.4 ± 6.4 years) and 159 non diabetic subjects (66 males / 93 females, mean age ± SD: 77.3 ± 5.2 years) hospitalized for ischemic stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…In this study there is mean hyperglycemia of (3.45±1.64) and (4.50±1.05) in those without stress hyperglycemia and this is statistically significant. 13 In the present study, predominantly male patients were affected in all the two groups. Akbar DH et al showed predominance in male among the diabetic and non-diabetic stroke patients and female predominance among the new hyperglycemic stroke patients.…”
Section: Study Resultssupporting
confidence: 46%
“…In this study there is mean hyperglycemia of (3.45±1.64) and (4.50±1.05) in those without stress hyperglycemia and this is statistically significant. 13 In the present study, predominantly male patients were affected in all the two groups. Akbar DH et al showed predominance in male among the diabetic and non-diabetic stroke patients and female predominance among the new hyperglycemic stroke patients.…”
Section: Study Resultssupporting
confidence: 46%
“…Several clinical and experimental studies have demonstrated that admission hyperglycemia has a deleterious effect on short term outcomes in acute stroke patients though some other studies have debated this [5][6][7]. Acute hyperglycemia in acute stroke is not always due to diabetes mellitus (DM) but may be due to stress response but the exact relationships as a cause or a consequence of more severe stroke remains controversial [8].…”
Section: Introductionmentioning
confidence: 99%
“…5, 51.5±4.3 and 45.3±2.1 among the diabetes, new hyperglycemic and non-diabetic stroke patients respectively. Athanasia et al in his study had a higher average age ranges in which the diabetic group had 77.4±6.4 years as compared to 77.3±5.2 years in the non-diabetic stroke group 9. …”
mentioning
confidence: 75%
“…Stress hyperglycemia has been studied in acute myocardial infarction and cerebrovascular event and its outcomes. 9 In spite of vastly available data and recent updates on stroke, there are no clear guidelines to support whether this hyperglycemia needs to be treated or not. Still controversies exist on whether this stress hyperglycemia is harmful and affect the outcome in acute ischemic stroke.…”
mentioning
confidence: 99%